1989
DOI: 10.1111/j.2044-8279.1989.tb03072.x
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Expectations in Infant School: Associations With Attainment and Progress, Curriculum Coverage and Classroom Interaction

Abstract: There is still much debate, particularly in North America, about whether teachers' expectations have an effect on pupils' achievement, and through which factors expectations might be mediated. This paper reports on associations between teachers' academic expectations at the beginning, and children's attainments at the end of the school year. The study took place in infant schools in London. Associations were significant during all three years of infant school, and were not explained by children's attainments a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 4 publications
0
14
0
1
Order By: Relevance
“…It is likely, for instance, that there will be other teacher variables contributing towards learning which require examination. For example, teaching styles will undoubtedly contribute towards children's learning (Blatchford, Burke, Farquhar, Plewis and Tizard, 1989). An examination of how time is allocated during lessons may also provide further and more detailed information about why certain teachers are perceived to be more effective than others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely, for instance, that there will be other teacher variables contributing towards learning which require examination. For example, teaching styles will undoubtedly contribute towards children's learning (Blatchford, Burke, Farquhar, Plewis and Tizard, 1989). An examination of how time is allocated during lessons may also provide further and more detailed information about why certain teachers are perceived to be more effective than others.…”
Section: Discussionmentioning
confidence: 99%
“…The role of teachers in the development of skills has also been studied with emphasis being placed on the effect of teachers' expectations on learner achievement -with low achievement and low teacher expectation being highly correlated (Rosenthal and Jacobson, 1968;and Blatchford, Burke, Farquhar, Plewis and Tizard, 1989). In music education research most of the investigations have focused on teachers delivering a curriculum in classroom contexts, where a single teacher works alone with a large group of children ( Cassidy, 1990;Duke and Madsen, 1991;Hendel, 1995;Madsen and Alley, 1979;Madsen and Geringer, 1989;Yarborough and Price, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The overall aim of the study was to investigate home and school influences on school progress. Earlier reports from the project have identified the effects of teacher expectations and curriculum coverage on pupils' school progress (Blatchford Blatchford et al, 1989;Tizard et al, 1988), as well as effects of preschool skills on attainment at 7 and 11 (Blatchford et al, 1987;Blatchford & Plewis, 1990), and pupils' views on academic work and school at 11 and 16 years (Blatchford, 1992b;Blatchford, 1996). As part of the study, pupils were interviewed at 7, 11 and 16 years and in the course of the interviews, academic self assessments and allied information were obtained.…”
Section: Introductionmentioning
confidence: 98%
“…In a comprehensive review, Good (1987) notes that pupils believed to be less capable have less opportunity to think and analyse, less autonomy and less choice on curriculum assignments. In similar vein, Blatchford et al (1989) found that low expectation infants in their second and third year of school were given a narrower curriculum coverage, subsequently becoming aware of teacher expectations and accordingly altering perceptions about themselves as learners. However, Brophy and Good (1974) have commented that susceptibility to teacher-expectation effects may be an individual difference variable and that more data are required to identify specific characteristics which make both teachers and children susceptible to such effects.…”
Section: Introductionmentioning
confidence: 85%